Analisis Faktor-Faktor yang Menyebabkan Terjadinya Gagal Klaim Asuransi pada PT. Prudential Cabang Binjai - Saidah Hayati Situmeang; Yusrizal Yusrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThis research aims to determine the producer for implementing claims handling at PT. Prudential Life Assurance Binjai. This research is a descriptive research with a qualitative approach. Data collection techniques used are interviews with insurance agents PT. Prudential Life Insurance Binjai and literature study. Based on the results of research and discussion, conclusions have been drawn. An insurance claim is a claim from the insured party in connection with a contract agreement between the insurance and the insured party, where each party binds itself to guarantee the payment of compensation by the insurer if the insurance premium payment has been made by the insured party when a disaster is suffered by the insured party. As for the stages of the claim being submitted, it must be completed with all the required complementary requirements and documents. If the requirements and documents are not complete, there will be a rejection from the insurance company.